Mobilities, communication and intercultural education: contemporary global challenges - Ramos, Natália (2023)
Migrations, interculturalism and digital and intercultural communication are domains heavily present in the social and political discourses of the last and fi rst decades of the 20th and 21st century, respectively, at the level of various sectors, and in the communication, intercultural and educational paradigms nowadays. Cultural diversity, a multicultural and network society, the Internet, the development of digital information and communication technologies, the inclusion of these technologies in education and teaching gave origin to new forms of relationship, communication and learning. They also gave origin to major changes in society and social organisations, particularly in education, environments where interculturalism and student mobility have been increasing. In this article, some of these questions will be discussed, which are raised in a contemporary framework, and we will also analyse policies, strategies and competences which may help professionals who work with migrants, refugees and ethnic/cultural minorities to better interact with this population, fostering their welcoming and social inclusion as well as promoting coexistence, communication and intercultural education, and the development and wellbeing of everybody, regardless of their cultural or social origin.